Identification of C-Reactive Protein from Gingival Crevicular Fluid in Systemic Disease - Amelia Surdu Macovei; Liliana Pasarin; Oana Potarnichie; Silvia Martu (Romanian Society of Oral Rehabilitation, 2012)
Periodontitis is associated with elevated C-reactive protein (CRP) in both serum and gingival crevicular fluid (GCF). Although the liver is the primary source of CRP, extra-hepatic production of CRP has been reported. This study aimed to determine whether CRP in GCF is produced locally in the gingivae. Material and methods Gingivae and GCF were collected from non-periodontitis and periodontitis sites. Presence of CRP in gingivae was assessed by immunohistochemistry. CRP in GCF was measured using ELISA. Gene expression for CRP in gingivae was determined using real-time polymerase chain reaction. Results CRP was found in both the gingivae and GCF. No gingivae had detectable amounts of CRP mRNA. Not all patients with periodontitis had detectable levels of CRP in the GCF. Some non-periodontitis patients had detectable levels of CRP in the GCF. Conclusions CRP in the GCF appears to be of systemic origin, and therefore may be indicative of systemic inflammation from either a periodontal infection or inflammatory disease elsewhere. The correlation between levels of CRP in GCF and serum requires validation in future studies.